Systematic literature review : Efektivitas penggunaan media digital sebagai instrumen evaluasi dalam Pembelajaran Kejuruan di SMK - Agraini, T Rahmilia; Ummah, Adisty Akhoma; Sari, Putri Mayang; Simantupang, Wakhinuddin; Yuliana, Yuliana (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Vocational education in Vocational High Schools (SMK) plays an essential role in equipping students with relevant skills. To ensure a successful learning process, regular evaluation is needed. This study aims to analyze the effectiveness of using digital media as an evaluation tool in vocational education at SMK. Using a systematic literature review method, this study examines various relevant scholarly articles on the implementation of digital evaluation media in vocational subjects at SMK. The findings indicate that digital evaluation tools, such as Wordwall, Quizizz, Edmodo, Kahoot, and Google Forms, play a significant role in improving student outcomes, engagement, and motivation. These digital tools facilitate interactive and efficient evaluation, support more adaptive and objective assessment processes, and provide faster feedback.